Customer satisfaction in dining experience in Continuing Care Retirement Communities and Retirement Communities - Generali, Heather (Kansas State University, 2010)
Abstract Aging has become a focal point for several segments of the foodservice industry with the forecasted trends. Due to the link between quality of life and satisfaction with food in this population, many Continuing Care Retirement Communities (CCRCs) and retirement communities are employing individuals who have experience in the hotel/restaurant industry. The purpose of the study was to assess residents’ overall satisfaction with quality of food and quality of service in Continuing Care Retirement Communities (CCRC) and retirement communities when the facility employs a foodservice director or chef with culinary training or expertise. The research compared satisfaction based on types of foodservices provided (restaurants and café/bistros); resident characteristics such as gender and length of time residing at a facility; frequency of interaction with the chef or foodservice director; and meal plan requirement. The study was conducted in the Midwest region and included a convenience sample of Retirement Communities and CCRCs in Kansas, Missouri and Nebraska. The variables analyzed were quality of food, quality of service, atmosphere, dining venues, meal plans, and frequency of dining with overall satisfaction. Atmosphere, food quality, dining venues, and meal plans significantly influenced overall satisfaction. Residents in facilities that provided more than one dining option had a slightly lower satisfaction ratings compared to the group who had one dining option. Overall satisfaction ratings for meal plan indicated that the respondents were neutral relative to the affect of meal plan and their overall satisfaction. The frequency of dining in one of the venues was positively influenced by meal plan requirements in the facilities. Residents who had lived in the facilities less than two years rated satisfaction higher. The more frequent the chef and foodservice manager interacted with the residents the higher the rate of overall satisfaction. Foodservice directors and administrators in these facilities can use the results to understand what the customers are looking for and how to improve overall services for their residents.
Keywords: Customer satisfaction, Continuing Care Retirement Community (CCRC), Retirement Community, Food Quality, Dining Venues; Business Administration, General (0310)